Prediction and prognostication of neurological deterioration in patients with acute ICH: a hospital-based cohort study. Issue 7 (28th July 2015) - Ovesen, Christian; Christensen, Anders Fogh; Havsteen, Inger; Krarup Hansen, Christine; Rosenbaum, Sverre; Kurt, Engin; Christensen, Hanne
Abstract : Objective: Patients with intracerebral haemorrhage (ICH) are at high risk of neurological deterioration (ND). We aimed at establishing predictors of early ND (END) as well as late ND (LND) and at exploring the impact of neurological stability during the first week on long-term prognosis. Design: We conducted this study as a retrospective cohort study. ND was evaluated based on the consciousness and severity of neurological symptoms. ND during the first 24 h after admission was defined as early ND and from 24 h to 7 days as LND. Patients were followed up until February 2015. Participants: We included 300 patients with acute ICH (≤4.5 h from symptom onset) who were admitted to our institution from March 2009 to January 2015. Setting: Section of Acute Neurology, Department of Neurology, Bispebjerg Hospital is a specialised referral centre receiving patients with acute stroke from the entire capital region of Denmark. Results: We found that a spot sign on CT angiography (OR 10.7 CI 4.79 to 24.3) and extensive degree of interventricular haemorrhage (IVH) (OR 8.73 CI 2.87 to 26.5) were independent predictors of END, whereas a degree of comorbidity (Charlton Index), admission stroke severity and degree of IVH predicted LND. On follow-up imaging, haematoma expansion was independently associated with END (OR 6.1 CI 2.2 to 17.3), and expansion of IVH was independently associated with both END (OR 1.7 CI 1.2 to 2.3 per point increase) and LND (OR 2.3 CI 1.3 to 4.2 per point increase). ND during the first week was associated with a 1-year mortality of 60.5%, compared with 9.2% among the patients who remained stable. Conclusions: These results suggest that stability during the first week entails an optimistic prognosis. A relatively easy and effective risk stratification of END and LND is possible on admission based on the spot sign, IVH and clinical parameters.